1999
DOI: 10.1152/ajpgi.1999.276.3.g629
|View full text |Cite
|
Sign up to set email alerts
|

Transplanted hepatocytes proliferate differently after CCl4treatment and hepatocyte growth factor infusion

Abstract: To understand regulation of transplanted hepatocyte proliferation in the normal liver, we used genetically marked rat or mouse cells. Hosts were subjected to liver injury by carbon tetrachloride (CCl4), to liver regeneration by a two-thirds partial hepatectomy, and to hepatocellular DNA synthesis by infusion of hepatocyte growth factor for comparative analysis. Transplanted hepatocytes were documented to integrate in periportal areas of the liver. In response to CCl4 treatments after cell transplantation, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(71 citation statements)
references
References 26 publications
7
64
0
Order By: Relevance
“…deposits hepatocytes into liver sinusoids (2)(3)(4)(5). The whole liver was radiated to 10-50 Gy with an orthovoltage x-ray machine (Philips Super M 100, Philips Medical Systems, Bothell, WA), as reported (16).…”
Section: Fig 1 Experimental Design (A)mentioning
confidence: 99%
“…deposits hepatocytes into liver sinusoids (2)(3)(4)(5). The whole liver was radiated to 10-50 Gy with an orthovoltage x-ray machine (Philips Super M 100, Philips Medical Systems, Bothell, WA), as reported (16).…”
Section: Fig 1 Experimental Design (A)mentioning
confidence: 99%
“…[20][21][22] Previous studies documented that transplanted hepatocytes can integrate into the host liver parenchyma [23][24][25] ; however, transplanted hepatocytes show very limited proliferative activity in the normal liver. 26 Studies in transgenic mice have shown that the liver can be repopulated by genetically engineered rodent hepatocytes harboring a selective growth advantage over resident hepatocytes. [27][28][29][30] The discovery of a liver-toxic phenotype in urokinase-type plasminogen activator (uPA) transgenic mice led to the development of a novel liver repopulation model, in which hepatocyte-targeted expression of the albumin-uPA transgene depletes host hepatocytes progressively.…”
mentioning
confidence: 99%
“…78 The remaining cells translocated from sinusoids into liver plates within 20 h after cell transplantation, through a process involving disruption of the sinusoidal endothelium, release of vascular endothelial growth factor (VEGF) by both host and transplanted hepatocytes. 77,79,80 Subsequently, translocated cells integrated into the liver parenchyma, regained their polarity with the formation of gap junctions and bile canaliculi between transplanted and host hepatocytes within about 1 week, without any significant proliferation in adult animals and were functional throughout the life of animals. 74,75,81 Overall, only 20-30% of transplanted hepatocytes integrated into the liver.…”
Section: Hepatocyte Transplantation Mechanismsmentioning
confidence: 99%
“…Partial hepatectomy and hepatocyte growth factor infusion were ineffective in increasing the transplanted hepatocyte mass, because both transplanted and host hepatocytes had been removed and/or responded equally to the regenerative stimuli. 41,80 In contrast, carbon tetrachloride (CCl 4 ) treatments increased the transplanted hepatocyte mass. 80 This is in agreement with the fact that CCl 4 selectively injured centrolobular hepatocytes, leading to the compensatory proliferation of portal hepatocytes, and that transplanted hepatocytes were mostly located in periportal areas.…”
Section: Strategies For Liver Repopulationmentioning
confidence: 99%
See 1 more Smart Citation